On Communication and Collusion - Awaya, Yu; Krishna, Vijay (American Economic Review, 2016)
We study the role of communication within a cartel. Our analysis is carried out in Stigler’s (1964) model of repeated oligopoly with secret price cuts. Firms observe neither the prices nor the sales of their rivals. For a fixed discount factor, we identify conditions under which there are equilibria with “cheap talk” that result in near-perfect collusion, whereas all equilibria without such communication are bounded away from this outcome. In our model, communication improves monitoring and leads to higher prices and profits. (JEL C73, D43, D83, L12, L13, L25)